THE IMPACT OF ACCOUNTING CONSERVATISM ON THE VALUATION OF PRIVATE IRAQI BANKS: A STUDY OF SELECTED BANKS LISTED ON THE IRAQI STOCK EXCHANGE - Ali Mirzah Abd- Alhamza Al-Iissawi (American Journals Publishing, 2024)
The research used Tobin's Q scale to measure the extent of accounting conservatism practices in private Iraqi banks and their impact on the company’s value. The study focused on twenty-three Iraqi banks listed on the Iraqi Stock Exchange from 2018 to 2022, with a sample size of fourteen banks, approximately 60% of the total population. The results revealed variations in accounting conservatism practices among the sampled banks based on profit skewness, with some banks implementing these practices while others did not. The researcher recommends that banks adhering to conservative practices should continue doing so while striving to strike a balance between high market value and book value. Achieving this balance is crucial for positive performance evaluation and efficient decision-making. Additionally, increasing accounting conservatism practices should be done in a way that provides more relevant information for decision-making and enhances the bank's value.
Keywords: Accounting, conservatism, company value.